Characterization of Intestinal Microbiota and Probiotics Treatment in Children With Autism Spectrum Disorders in China - Niu, Manman; Li, Qinrui; Zhang, Jishui; Wen, Fang; Dang, Weili; Duan, Guiqin; Li, Haifeng; Ruan, Wencong; Yang, Pingri; Guan, Chunrong; Tian, Huiling; Gao, Xiaoqing; et al. (Frontiers in Neurology, 2019)
Background: Most previous studies have found that human intestinal microbiota affect the symptoms of autism spectrum disorder (ASD), especially gastrointestinal (GI) symptoms, but there is limited data of non-western ethnicity. Probiotics can reconstitute the host intestinal microbiota and strengthen gastrointestinal function, whereas it lacks clinical data proving the effect of probiotics treatment for ASD. Methods: This study explored the significant differences between ASD and neurotypical (NT), and the improvement of applied behavior analysis (ABA) training in combination with probiotics versus ABA training only. Results: We found significant differences between the ASD group and the NT group in the evenness of the intestinal microbiota and the relative abundance of the bacterial phyla and genus. At the phylum level, relative abundance of Bacteroidetes in the ASD group was significantly lower than in the NT group. At the genus level, the relative abundance of Bacteroides, Bifidobacterium, Ruminococcus, Roseburia, and Blautia in the ASD group was significantly lower than that in the NT group. After 4-week ABA training program in combination with probiotics treatment, the ATEC and GI scores decreased more than the control group with ABA training only. Conclusion: Our ﬁndings suggest that intestinal microbiota is different between the NT children and the ASD children with or without GI. In combination with ABA training, probiotics treatment can bring more benefit to ASD children. Clinical trials with a more rigorous design and larger sample size are indispensable for further validation.